ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMBANGUNAN LAUNDRY ZEST HOTEL - Latuconsina, Zainab; Metekohy, Selly; Langi, Jeffrey Payung (Journal Agregate, 2024)
In the world of construction services, labor productivity is one of the determining factors for the success of a development project. It measures the success or failure of a construction project in achieving its objectives. One way to increase worker productivity comes from worker attitudes by increasing worker commitment, satisfaction, and responsibility for work. Therefore, in efforts to analyze labor productivity, variables that might influence the level of productivity must be considered. This research was conducted to find out what factors influence labor productivity and to determine the influence of labor characteristic factors on worker productivity. The research was carried out by observing the productivity level of 15 workers and accompanied by filling out a questionnaire. From the data collection results, both productivity data and questionnaires were processed using the SPSS (Statistical Package for Social Science) version 26 computer program. Based on the results of the analysis of factors that influence productivity, including skill diversity (x1). task identity (x2) variable task significance (x3). Based on the results of hypothesis testing, skill diversity has a positive effect on productivity with a positive T count value of 2.630 > 2.160. Task identification has a positive effect on productivity with a calculated T value of 2.435 > 2.160. Task significance hurts work productivity with a calculated T value of -2.384 < -2.160. Based on the R square test, it can be seen that the characteristics of the workforce consisting of the variables skill diversity, task identity, and task significance simultaneously influence productivity with a multiple determination coefficient values of 84%, and the remaining 8.4% is influenced by other variables not included in this research.